Kriopreservasi Tunas in Vitro Pepaya ‘Sukma’ Dengan Perlakuan Prakultur, Loading, Dan Dehidrasi Dengan Pvs2 Dan Modifikasinya - Fitri Fatma Wardani; Joko Ridho Witono; Darda Efendi; Diny Dinarti (BERITA BIOLOGI, 2021)
Papaya has high genetic variability because it is an open-pollinated plant and has genotype and phenotypeare that are easily changed due to environment changes. Cryopreservation is a storing method of germplasm in liquid nitrogen (-196 oC) which can maintain the genotype and phenotype of germplasm. The experiment aimed to obtain the best preculture, loading, and dehydration for cryopreservation of papaya ‘Sukma’ in vitro shoots. For preculture, we planted shoots on MS media with 0.3 M and 0.4 M sucrose for 1, 2, and 3 days. In the loading treatment, we immersed shoots in loading solution (liquid MS+1.2M glycerol+0.4M sucrose) for 0, 10, 20, and 30 minutes. For dehydration, we immersed shoots in cryoprotectant (PVS2 and its modification) for 5, 10, and 15 minutes. Then, shoots were immersed in liquid nitrogen. The results showed thatshoots had the best survival rate while they had been precultured on MS medium with 0.3 M sucrose for 3 days. The best loading treatment time was 20–30 minutes. The best dehydration treatment was obtained by modification of PVS2 for 10 minutes. The shoots have not been able to recovery after cryopreservation, so it can be concluded that cryopreservation of in vitro papaya ‘Sukma’ shoots has not been successful.